LEADERSHIP OF 5-6 YEAR OLD CHILDREN AND ITS ASSESSMENT CRITERIA - Nagle-Baranova, Baiba (Education Reform: Education Content Research and Implementation Problems, 2024)
The research aim is analyze theoretical literature to ascertain the relevance of leadership skills of 5-6-year-old children and leadership assessment criteria. When comparing and analyzing the information provided in various studies, the leadership abilities of adults and educators are more often emphasized. The content of competence education reveals how important it is to develop leadership skills in preschool children. During the research, it was concluded that the leadership skills of adults are equivalent to the typical skills of 5-6-year-old children, which develop at this age. Several of these skills are learned by integrating cross-cutting skills into the pedagogical process. As a result of the theoretical analysis, six leadership evaluation criteria and 4 levels of 5-6-year-old children were identified. Children who have developed their leadership skills are more successful in the next stages of education. According to the summary of the results, it can be concluded that every 5-6-year-old child possesses leadership skills to a greater or lesser extent, it is important to notice these skills in time and continue further development based on children's strengths.